Quality Parameters and Fermentation Characteristics of Ensiled Water Hyacinth(Eichhornia crassipes) - Hundal, J.S.; Singh, Digvijay; Ansal, Meera D.; Chahal, Udeybir Singh; Kaur, Vaneet Inder; Sharma, Amit (Indian Journal of Animal Nutrition, 2025)
The present study was conducted to explore the nutritional potential of wilted Water Hyacinth silage as an unconventional feed resource. A total of seven Water hyacinth silage; six were wilted viz. T1 (Eichhoria 75%+ rice straw 16%+ molasses 4%) T2 (Eichhoria 75%+ rice straw 15.5+ molasses 4%+Urea 0.5%); T3 (Eichhoria 75%+ rice straw 10%+ molasses 4%+ wheat bran 6%); T4 (Eichhoria 75%+ rice straw 10%+ molasses 4%+ moringa 6%); T5 (Eichhoria 65 %+ rice straw 25%+ molasses 4%); T6 (Eichhoria 65% + rice straw 25%+ molasses 4% and Urea 1%) and one without wilting T7 (Eichhoria 95%) were prepared. The addition of 10% Rice straw + 6 % WB or 6% moringa (T3 and T4) increased (P